Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Terhadap Keputusan Penggunaan Jasa Pada Rumah Sakit Umum Daerah (RSUD) Waluyo Jati Kraksaan Kabupaten Probolinggo - Herlin Herawati (Ecobuss, 2016)
This study was conducted at Hospital Waluyo Jati Kraksaan with the aim to determine the effect of service quality and customer satisfaction to the decision on the use of hospital services Waluyo Jati Kraksaan simultaneously and partially, and to determine the variables between service quality and customer satisfaction are the most dominant influence on decision the use of services from hospitals Waluyo Jati Kraksaan. This type of research is explanatory research, the variables which were used independent variables such as quality of service and customer satisfaction, and the dependent variable that decision the use of hospital services. Samples used as many as 69 people, and the method of data analysis using quantitative analysis method using statistical formulas in the form of multiple regression analysis, multiple correlation, coefficient of determination and hypothesis testing and processing using SPSS v.16.. Keywords : quality of service, customer satisfaction, the use of hospital services.